ผลของการเสริมสร้างพลังอำนาจโดยหัวหน้าหอผู้ป่วย ต่อความเป็นอิสระแห่งตนและความพึงพอใจในงานของพยาบาลประจำการ - ศิริพร พูนชัย (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
To compare personal autonomy and job satisfaction of staff nurses before and after using empowerment by head nurses. Research subjects consisted of 22 staff nurses who were equally divided into one experimental group and one control group. Nurses in the experimental group worked with their head nurse using the empowerment program which composed of nursing conferences and group process activities for 4 weeks. Five instruments, developed by the researcher, were an empowerment manual, a test for knowledge on empowerment and three questionnaires which were designed to measure empowerment, personal autonomy, and job satisfaction. These tools wee tested for content validity. The internal reliability of a test and three questionnaires were .84, .92, .73 and .89, respectively. Statistical techniques which were used in data analysis were percentage, mean, standard deviation and t-test. Major results were as followed :- 1. There was no significant difference between the personal autonomy of staff nurses before and after being empowered by their head nurse, for 4 weeks. 2. The personal autonomy of staff nurses after being empowered by their head nurse for 10 weeks, was significantly higher than that before being empowered, at the .05 level. 3. There was no significant difference between the job satisfaction of staff nurses before and after being empowered by their head nurse for 4 weeks and for 10 weeks.